Pengaruh Program Senam Lansia dalam Menurunkan Kadar Gula Darah pada Lansia di Puskesmas Nibong - Nur Mulia; Hafni Zahara; Mansura Feby Amanda (Pusat riset dan Inovasi Nasional, 2026)
Elderly exercise is a sporting activity that can help improve heart health, maintain stable blood pressure and blood sugar levels, and prevent various degenerative diseases in the elderly. Abnormal blood sugar levels can cause metabolic disorders that lead to various serious health problems. This study aims to determine the impact of elderly exercise on improving the health and independence of older adults in carrying out daily activities. This study used an evaluative method with a cross-sectional approach at the Nibong Community Health Center, North Aceh, involving 38 elderly people (14 men and 24 women) as a sample. The results showed that after participating in regular exercise, the number of elderly people with high blood sugar levels decreased to 31.6%, while the number of elderly people with normal blood sugar levels increased to 86.6%. Statistical tests showed a significant difference between blood sugar levels before and after exercise (p < 0.05). From these results, it can be concluded that elderly exercise is effective in lowering blood sugar levels, increasing insulin sensitivity, improving fitness and balance, and motivating elderly people to maintain their health. It is recommended that the Nibong Community Health Center regularly hold structured elderly exercise programs and provide educational counseling on the importance of a healthy lifestyle and controlling sugar intake. The results of this study can serve as a reference for health institutions and further research